Recovery Responses of Central Hemodynamics in Basketball Athletes and Controls After the Bruce Test - Zhang, Yahui; Qi, Lin; van de Vosse, Frans; Du, Chenglin; Yao, Yudong; Du, Jianhang; Wu, Guifu; Xu, Lisheng (Frontiers in Physiology, 2020)
Purpose: It is commonly believed that central hemodynamics is closely associated with the presence of cardiovascular events. However, controversial data exist on the acute response of competitive sports on central hemodynamics. Moreover, the central hemodynamic response to exercise is too transient to be investigated. Therefore, this study aimed to investigate the central hemodynamic response in young basketball athletes and controls in 1-h recovery after exercise. Methods: Fifteen young basketball athletes and fifteen aged-matched controls were recruited to perform the Bruce test. Central hemodynamics were measured and calculated, including heart rate (HR), aortic systolic, diastolic and pulse pressure (ASP, ADP and APP), ejection duration (ED), sub-endocardial viability ratio (SEVR), central augmentation index (AIx) and AIx@HR75. Intra-group and inter-group differences were analyzed by two-way repeated measures ANOVA. Results: ASP significantly decreased at 10min after exercise in athletes, while it markedly declined at 15min after exercise in controls (p<0.01). Additionally, only in the athlete group, ADP significantly decreased at 50min and at 1-h after exercise. AIx was also significantly reduced at 1-2min, 20min, 30min and 40min after exercise (all p<0.05). Moreover, there were significant differences in the changes of these parameters between the two groups at those measurement points (p<0.05). SEVR significantly recovered to baseline level at 30min, while ED and HR returned to baseline levels at 40min after exercise in both groups. Conclusions: Sustained decrease of aortic BPs was sooner after the cessation of exercise in athletes than that in controls, and changes of aortic stiffness were more evident in athletes than those in controls during the 1-h recovery period. Additionally, SEVR returned to the baseline sooner than ED and HR in athletes.